PENINGKATAN KETERAMPILAN BERBICARA SISWA MENGGUNAKAN METODE PEMODELAN DI SEKOLAH DASAR - Zurindayu, Yesenia; Halidjah, Siti; Asran, Mastar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractCommon problem in this research is whether by using modeling method can improve speech skill at third grade student of Sekolah Dasar Negeri 34 Pontianak Kota?. The general purpose of this study is to describe the use of modeling methods that can improve the speaking skills of third grade students of State Elementary School 34 Pontianak Kota. This research uses descriptive method with class action research form, and the nature of research is collaborative. Setting the research took place at the State Elementary School 34 Pontianak Kota with the subject of the study of students class III C which amounted to 31 people. Data collection techniques used are interview techniques, direct observation techniques, measurement techniques with data collection tool that is the observation sheet. The data collected in the analysis with the average calculation. This research was conducted 3 cycles. In cycle I the average score of students is 73,23. While in cycle II the average value of students to 76.45 increased by 3.22. In cycle III the average score of 81.61 students increased by 5.16. With the implementation of modeling methods in learning Indonesian language can improve speaking skills, so it can be concluded that the use of modeling methods can be used to improve the ability of speaking class III students in SD Negeri 34 Pontianak Kota.Â Keywords: Improvement, Speech Skills, and Modeling MethodsÂ